The Value of Advanced Subject Degrees in Addition to an MLS: An Updated Study - Day, Lance; Szurek, Jaroslaw (Portal (Baltimore, Md.), 2025)
This article builds on a 2018 study and reports on a survey conducted in 2022 to examine the value of advanced subject degrees in addition to the Master of Library Science for academic librarians. This study explores the impact of advanced subject degrees on scholarly contributions, compensation, teaching roles, and tenure status in academic librarianship. Research findings offer insights into compensation, perceptions of preparedness for research and publication, tenure status, and teaching credit-bearing courses among academic librarians with and without an additional advanced subject degree.